Analysis of Distribution and Marketing Margins of Sunu Grouper (Plectropumus leoparsus) in Teluk Sulaiman Village, Biduk-Biduk District, Berau Regency - Agustina, Eva; Haqiqiansyah , Gusti; Juliani, Juliani (Nusantara Tropical Fisheries Science (Ilmu Perikanan Tropis Nusantara), 2023)
The study was conducted with the aim of analyzing and describing how the distribution process and marketing margins of Sunu Grouper (Plectropomus leopardus) in Sulaiman Bay Village. The research was carried out for 9 months from March to December 2022 in Kampung Teluk Sulaiman, Biduk-Biduk District, Berau Regency. The method used in sampling fishermen is purposive sampling with a total of 21 respondents, while in sampling collecting traders and retailers using the snowball sampling method as many as 10 people. The analysis method uses qualitative descriptive analysis. The results show that the marketing channel pattern on the sale of Sunu Grouper Fish in Kampung Teluk Sulaiman there are 2 levels of marketing channels of the level one channel pattern and the second level channel pattern. Based on the results of the margin calculation of each Sunu Grouper marketing institution in Teluk Sulaiman village, the institutions that obtained a larger margin were collecting traders of IDR 25,000, while retailers of IDR 20,000